Gaya Mengajar Inklusi dalam Meningkatkan Hasil Belajar Pukulan Forehand Drive Tenis Meja pada Siswa Sekolah Menengah Pertama. - Rizky, Vicky; Damanik, Suryadi; Siregar, Samsuddin (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2021)
The purpose of the study. To determine the magnitude of increase in learning outcomes obtained forehand drive class VIII SMP Negeri 9 Binjai 2019/2020 through inclusion of teaching styles. Materials and methods. The sample in this study were 38 students of class VIII. To analyze the data in this study and to find out the results seen from the students' completeness individually and classically. The research method used is a classroom action research method. In this study, a learning outcome test was carried out in the form of a portfolio, with the inclusive teaching style method, then a learning outcome test was held in cycle I and cycle II in the form of performing the basic technique of Forehand Drive Punch. Results. The results of the initial tests conducted on class VIII students of SMP N 9 Binjai. Of the 38 students there were 11 students (27.64%) who had reached the level of mastery learning with an average value of student learning outcomes of 64.90%. The results of the first cycle, there were 19 students (50%) of 38 students, who had reached the level of completeness of learning with an average value of student learning outcomes 68.41%. In cycle II there are 33 students (86.84%) of 38 students who have reached the level of learning completeness with an average value of 80.04. Conclusions. The results of the initial tests of student learning to do the first cycle and the second cycle increased, danpat said through inclusion style of teaching can improve student learning outcomes.